Principles of cell biology - Plopper, George (Jones & Bartlett Learning, 2013)
"Written for the undergraduate cell biology course, Principles of Cell Biology provides students with an accessible approach to the fundamental concepts of cell biology. With a concept-based method, the text focuses on the underlying principles that illustrate both how cells function and how we study them. It identifies 10 principles of cell biology and devotes a separate chapter to illustrate each. The result is a shift away from the traditional focus on technical details and toward a more integrative view of cellular activity that is flexible and can be tailored to suit students with a broad range of backgrounds. An informal, narrative writing style makes even the most complex concepts accessible to students new to the scientific field. With a wealth of student and instructor ancillary items to round out the course, Principles of Cell Biology is the clear choice for your students." -- cover.